AOTT 2022
DOI: 10.5152/j.aott.2022.22091
|View full text |Cite
|
Sign up to set email alerts
|

Intralesional curettage and cementation of low-grade chondrosarcomas of the appendicular skeleton: Long-term results from a single center

Abstract: Objective: The purpose of this study was to investigate the results and complications in patients who had low-grade chondrosarcomas in the appendicular skeleton and were treated by intralesional curettage and cementation within the scope of 25 years of experience in a single center. Methods: Ninety-one patients (72 female and 19 male) were retrospectively analyzed. The median at the time of surgery was 43 (17-78) years, and the median follow-up was 102 (26-288) months. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Unfortunately, most of them, including Hedgehog inhibitors that elicited good pre-clinical responses, failed to demonstrate a survival benefit when translated into clinical trials [ 38 ]. Although recent studies have demonstrated good short-term results after intralesional surgical procedures for low-grade ChSs treated with curettage and adjuvant treatments consisting of phenol application, cauterization, or cryotherapy, the primary and preferred treatment for ChS patients with localized disease remains radical surgical resection with wide margins [ 27 , 39 , 40 , 41 ]. Of note, for the management of extremity ChSs, amputation is only reserved for patients with extensive and invasive disease [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, most of them, including Hedgehog inhibitors that elicited good pre-clinical responses, failed to demonstrate a survival benefit when translated into clinical trials [ 38 ]. Although recent studies have demonstrated good short-term results after intralesional surgical procedures for low-grade ChSs treated with curettage and adjuvant treatments consisting of phenol application, cauterization, or cryotherapy, the primary and preferred treatment for ChS patients with localized disease remains radical surgical resection with wide margins [ 27 , 39 , 40 , 41 ]. Of note, for the management of extremity ChSs, amputation is only reserved for patients with extensive and invasive disease [ 42 ].…”
Section: Introductionmentioning
confidence: 99%